2011
DOI: 10.5802/aif.2682
|View full text |Cite
|
Sign up to set email alerts
|

Maximal compatible splitting and diagonals of Kempf varieties

Abstract: Lakshmibai, Mehta and Parameswaran (LMP) introduced the notion of maximal multiplicity vanishing in Frobenius splitting. In this paper we define the algebraic analogue of this concept and construct a Frobenius splitting vanishing with maximal multiplicity on the diagonal of the full flag variety. Our splitting induces a diagonal Frobenius splitting of maximal multiplicity for a special class of smooth Schubert varieties first considered by Kempf. Consequences are Frobenius splitting of tangent bundles, of blow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…It follows that σ splits the p th power morphism on R(L) and hence is a graded splitting of R(L). We also recall the following essential result from [1], [16].…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations
“…It follows that σ splits the p th power morphism on R(L) and hence is a graded splitting of R(L). We also recall the following essential result from [1], [16].…”
Section: 2mentioning
confidence: 96%
“…By Lemma 3.1, H 0 ≥m (2(p − 1)ρ) is the subspace of H 0 (2(p − 1)ρ) consisting of elements that vanish to multiplicity at least m at the identity in G/B. It follows by Lemma 2.12 in[16] that a splitting section s ∈ H 0 (2(p − 1)ρ) maximally compatibly splits the identity if and only if s ∈ H 0 ≥(p−1)N (2(p − 1)ρ).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…At the same time it was observed that this "canonical" Frobenius splitting would not work in general. Recently Lauritzen and Thomsen [6] introduced a new Frobenius splitting of X × X, for X = SLn(k) /B, with the desired vanishing property along the diagonal. As a consequence the LMP-conjecture is now verified for any generalized flag variety of the form SL n (k) /P .…”
Section: Introductionmentioning
confidence: 99%
“…This conjecture has been considered by several authors (see for example [15], [12], [5], [13], [18]). In particular Brown and Lakshmibai in [5] proved this conjecture for minuscule homogeneous varieties using Representation Theoretic techniques and a case by case analysis.…”
Section: Introductionmentioning
confidence: 99%